2018
DOI: 10.29303/jp.v8i1.79
|View full text |Cite
|
Sign up to set email alerts
|

AKTIVITAS ENZIM PENCERNAAN UDANG VANAME (Penaeus vannamei) YANG DIBERIKAN PAKAN BERBAHAN BAKU TEPUNG Skeletonema costatum

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh  penggunaan tepung Skeletonema costatum  dalam berbagai dosis untuk mensubstitusi tepung ikan dalam pakan terhadap peningkatan aktivitas enzim protease dan amilase pada udang vaname (Penaeus vannamei). Pakan yang diberikan adalah isoprotein 37% dan iso energy 3.6 kkal/g pakan. Penelitian menggunakan Rancangan Acak Lengkap dengan dengan 4 perlakuan dosis tepung skeletonema sebagai pengganti tepung ikan yaitu A=0%; B=2.5%; C=5%, dan D=7.5% dengan ulanga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Amylase was measured based on Lestari (2018) and Al Gadri, Untung & Priyanto (2014) using the formula below. Sample, control and blank were checked in spectrophotometer at 540 nm.EA=[AB]×N0.333333emNaOH×1000VE×t…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amylase was measured based on Lestari (2018) and Al Gadri, Untung & Priyanto (2014) using the formula below. Sample, control and blank were checked in spectrophotometer at 540 nm.EA=[AB]×N0.333333emNaOH×1000VE×t…”
Section: Methodsmentioning
confidence: 99%
“…This proved that shrimp in treatment B gets a higher enzyme activity, linear with their growth. Based on Lestari (2018), vaname shrimp is omnivore and high protease activity related to shrimp digesting protein activity.…”
Section: Digestive Enzymesmentioning
confidence: 99%
“…The previous study revealed that gel filtration chromatography was able to separate amylase enzyme from the digestion of Vannamei shrimp was 2.97 ± 0.11 units/mL (5). Other studies showed that amylase activity isolated from *Corresponding Author: hanifah_rahmi@uhamka.ac.id…”
Section: Introductionmentioning
confidence: 99%